PENGARUH KEDISIPLINAN TERHADAP PRESTASI SISWA SMAN 1 BENAI KABUPATEN KUANTANG SINGINGGI (STUDY KASUS KELAS IX) - ", Solihin; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This paper submitted to qualifies for bachelor’s degree of sociologist. With title “The Influence of Student Discipline Against Student Achievement of SMAN 1 Benai Kuantan Singingi District”. This research proposed to determine the influence of student discipline against their achievement. The students discipline could be seen based on the indicator of student achievement at school and their discipline at home. There are sub-indicator of student discipline at school is seen by their presence at school, time they arrived at school, done the homework, follow the lessons in school, and adhere to the school rules. While the sub-indicator of student discipline at home is seen by the regularity in learning, time allocation for study and doing homework at home. Student achievement is seen by the average value obtained on student report cards while sitting in class XI. This research is using quantitative descriptive method to examine the taken issue. Sample which be used on this research is 56 respondents out of 244 students. Sampling is using proportional random sampling. Data collection techniques were used are observation, questionnaire and documentation. And also present the results of processing data in tabular form. Theories used on this research are conformity, differential association, social control and achievement motivation. Based on this research, the influence of student discipline against the student achievement of SMAN 1 Benai is less influence. This is caused by for good achievement not only could be reached by discipline factor but also many other factors which have to met such as motivation, intelligence and others.Key words: Discipline, Achievement, Student of SMAN 1 Benai